Pursuing the Best Management Strategies for Corn-Soybean Rotation Systems in North Central Kansas - A. A. Correndo; I. A. Ciampitti (Kansas Agricultural Experiment Station Research Reports, 2019)
The aim of this study was to evaluate different management strategies for improving yield productivity in corn (Zea maysL.) and soybean [Glycine max(L.) Merr.] rotation systems. During the 2018 season, a long-term corn-soybean experiment was continued in Scandia, KS, evaluating five management strategies under rainfed and irrigated conditions. For corn, average yields were 146 bu/a and 172 bu/a under rainfed and irrigated conditions, respectively. For soybean, rainfed and irrigated average seed yields were similar (47–50 bu/a), attributed to herbicide injury on the irrigated plots. For both crop and water scenarios, intensifying the crop management (by modifying seeding rate, row spacing, fertilization program, and pest control) significantly increased yields as compared to the farmer’s strategies.
Keywords: yield gap; maize; rotation; productivity